MG53 Inhibits Necroptosis Through Ubiquitination-Dependent RIPK1 Degradation for Cardiac Protection Following Ischemia/Reperfusion Injury - Wang, Qiang; Park, Ki Ho; Geng, Bingchuan; Chen, Peng; Yang, Chunlin; Jiang, Qiwei; Yi, Frank; Tan, Tao; Zhou, Xinyu; Bian, Zehua; Ma, Jianjie; Zhu, Hua (Frontiers in Cardiovascular Medicine, 2022)
Rationale While reactive oxygen species (ROS) has been recognized as one of the main causes of cardiac injury following myocardial infarction, the clinical application of antioxidants has shown limited effects on protecting hearts against ischemia–reperfusion (I/R) injury. Thus, the precise role of ROS following cardiac injury remains to be fully elucidated. Objective We investigated the role of mitsugumin 53 (MG53) in regulating necroptosis following I/R injury to the hearts and the involvement of ROS in MG53-mediated cardioprotection. Methods and Results Antioxidants were used to test the role of ROS in MG53-mediated cardioprotection in the mouse model of I/R injury and induced human pluripotent stem cells (hiPSCs)-derived cardiomyocytes subjected to hypoxia or re-oxygenation (H/R) injury. Western blotting and co-immunoprecipitation were used to identify potential cell death pathways that MG53 was involved in. CRISPR/Cas 9-mediated genome editing and mutagenesis assays were performed to further identify specific interaction amino acids between MG53 and its ubiquitin E3 ligase substrate. We found that MG53 could protect myocardial injury via inhibiting the necroptosis pathway. Upon injury, the generation of ROS in the infarct zone of the hearts promoted interaction between MG53 and receptor-interacting protein kinase 1 (RIPK1). As an E3 ubiquitin ligase, MG53 added multiple ubiquitin chains to RIPK1 at the sites of K316, K604, and K627 for proteasome-mediated RIPK1 degradation and inhibited necroptosis. The application of N-acetyl cysteine (NAC) disrupted the interaction between MG53 and RIPK1 and abolished MG53-mediated cardioprotective effects. Conclusions Taken together, this study provided a molecular mechanism of a potential beneficial role of ROS following acute myocardial infarction. Thus, fine-tuning ROS levels might be critical for cardioprotection.